Avaliação dos efeitos da adição de óleos vegetais como substitutos de gordura animal em mortadela - Yunes, João Felipe Ferraz (2010)
The goal of this work was to develop mortadellas replacing porcine fat with canola, linseed soy and olive oils, using two different substitution levels (50% and 100%) and its evaluation based on fatty acids profile, nutritional quality, cholesterol amount, quality characteristics, oxidative stability and microstructure profiles. In the first experiment it was determined the fatty acid composition, the proportion between PUFA (poliunsaturated fatty acids)/SFA (saturated fatty acids) and also cholesterol content of the treatments control (P), linseed 50% (L1), linseed 100% (L2), canola 50% (C1), canola 100% (C2), olive 50 %(O1), olive 100% (O2), soy 50% (S1) e soy 100% (S2). The PUFA content had increased in all treatments with vegetable oils. For SFA, the control (P) had shown higher amounts and the treatments with canola oil had shown lower amounts. The treatments with vegetable oils also had shown higher ratio PUFA/SFA in comparison to control, and its cholesterol content were comparatively lower comparing to the control. About the second experiment, it was evaluated the substitution effect the oils of canola, linseed, olive and soy using two different substitution levels (50% and 100%) replacing porcine fat. This evaluation was based on quality characteristics, oxidation stability (TBARS value), and microstructure. All treatments had shown appropriated values regarding chemical and physicals parameters, in agreement with the Brazilian food legislation, good sensory scores, good texture and color profiles measured by devices, microbiological counting similar between control and other treatments and good stability against oxidation during shelf life. About the microstructure profile, any change in the emulsion had not been found. It is possible to find a correlation between the amount of fat seen in the pictures and the value obtained by the analytic method.